ANALYSIS OF NOISE INDUCED HEARING LOSS AT JUANDA INTERNATIONAL AIRPORT WORKER - Ario Ramadhan (Journal of Industrial Hygiene and Occupational Health, 2019)
Efforts to improve the quality of the world of aviation must cover aspects of Occupational Safety and Health (OSH) in every aspect of its planning. One of the airports that have implemented OSH is Surabaya Juanda International Airport. Based on the HIRARC analysis conducted by the SMS and OSH Department, Juanda International Airport, Surabaya is known to have the highest risk value, there was noise. Data obtained from the results of hazard identification and risk assessment using the HIRARC method and the results of noise measurements directly at the airport terminal 1 and 2 operations with a Sound Level Meter tool. Data analysis was carried out by comparing the results of measurements with Minister of Manpower and Transmigration Regulation Number 5 Year 2018 concerning Environmental Safety and Health. At Airside Terminal 1, the highest noise intensity was in the PS 11 area of 77 dBA (distance of 100 m) and 66 dBA (distance of 150m). At Airside Terminal 2, the highest noise intensity is in the area of PS A8 which is 80 dBA (distance 100 m) and 69 dBA (distance 150 m). Based on Minister of Manpower Regulation Number 5 Year 2018 concerning Work Environment Safety and Health, the noise intensity in Airside terminals 1 and 2 does not exceed the predetermined Threshold Value of 85 dBA with an exposure time of 8 hours. The Surabaya Juanda International Airport Manager should provide information on the importance of using PPE and implement the Hearing Conservation Program (HCP).